Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1111/j.1651-2227.1988.tb10660.x
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Effect of Obstetric (Neonatal) Brachial Plexus Palsy

Abstract: We have studied the causes and outcome of obstetric brachial plexus palsy in all children born in Malmö during the 10-year period 1973-1982. Forty-eight of 25,736 live-born children (0.19%) were neonatally diagnosed as having a brachial plexus paresis. Twenty-five percent of these, i.e., one child in 2,000 liveborn, had a persistent palsy. The obstetric history was characterized by high birthweight, vertex presentation with shoulder dystocia and multiparity; and in two cases the mother had two children with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
8

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(114 citation statements)
references
References 5 publications
5
101
0
8
Order By: Relevance
“…Forty-eight children were identified with NBPP [11]. Thirteen (27%) of these children had permanent sequela and four (8%) were considered to be 'almost well' by 12-18 months of age [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-eight children were identified with NBPP [11]. Thirteen (27%) of these children had permanent sequela and four (8%) were considered to be 'almost well' by 12-18 months of age [11].…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six children (96%) were classified into group I and II and two children (4%) were classified as group III and IV [11]. Both children in group III and IV were found to have permanent disability [11]. Of those with NBPP, 73% recovered and, if the 'almost recovered' children were included as part of the permanent palsies, only 65% showed complete recovery [11].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of OBPP is between 0.5% and 5 ‰ in countries with well developed obstetric services (6)(7)(8)(9)(10)(11)(12). Reduction in incidence from 1.56 per 1000 live births in 1938 to 0.28 per 1000 in 1962 was reported in New York.…”
Section: Incidencementioning
confidence: 99%
“…The authors ascribed the reduction to improved obstetric practice (13). Subsequent reports, including two population-based studies from Sweden (10,11), have suggested an increase in the incidence, possibly due to an increase in mean birth weight (10,11,(14)(15)(16). However, the incidence in the United Kingdom and Ireland has not changed in nearly 40 years (17).…”
Section: Incidencementioning
confidence: 99%
“…Although other studies found multiparity to be a significant risk factor, 15,16 its high prevalence in our population was found equally in both groups. Although the association with high birthweight, cephalic presentation and dystocia was found in other studies, [15][16][17] the association with maternal diabetes was only reported in one other study, 16 and no previous reports have shown a correlation with fetal distress, meconium-stained liquor, neonatal depression, maternal perineal lacerations or episiotomy, factors that might indicate difficult labor and fetal hypoxic-ischemic compromise. The great majority of infants (97.3%) recovered normal brachial plexus function except one (2.7%), who has persistent weakness after four years.…”
Section: Brachial Plexus Palsymentioning
confidence: 80%